MODERN MANAGEMENT OF DUODENAL VARICEAL BLEEDING - Farooqi, Amer Rehman; Sunderraj, Lawrence (Journal of Ayub Medical College Abbottabad, 2017)
Duodenal variceal bleeding is an uncommon cause of gastrointestinal bleeding. Treatment strategies are reliant on case reports and case series with new developments in interventional treatment modalities including endoscopic therapy, radiological intervention, and surgery. Endoscopic treatment includes injection sclerotherapy using various agents, banding of varices and clipping of varices. Interventional radiological procedures include Transjugular Intrahepatic porto-systemic shunt (TIPSS), and Balloon-Occluded Retrograde Transvenous Obliteration (BRTO). Surgical treatment could be suture ligation of varices or gastro-duodenectomy. In this article, a case report of upper gastrointestinal bleed, and management of duodenal varices is described, with review of the literature to offer optimum modern era treatment to these high risk gastrointestinal bleeds. Keywords: Variceal Clips; TIPSS; Ectopic varices; Portal Hypertension; Duodenectomy